Life Unsettled : A Scriptural Journey for Wilderness Times - Driver, Cory Thomas Pechan (Book collections on Project MUSE., 2021)
"Increasingly, many Christians and spiritual seekers feel they are in a sort of wilderness space where the familiar, settled, and normal parts of life have become unsettled, out of balance. More and more people are evaluating their lives and asking, "Where to now?" In Life Unsettled, Cory Driver uses the metaphor of wilderness journeying (a hallmark of the life of faith across the millennia) and the study of biblical texts, ancient Jewish legends, modern theological insights, and his own personal journeys to provide a guide for moving forward when we feel lost and confused. The biblical book of Numbers takes center stage in the author's creative musings about life in the wilderness. The Hebrew title of Numbers is Bemidbar, which means "In the Wilderness." In this oft-overlooked book are stories of God's passionate intimacy and anger, communal formation and struggles, and personal failures and triumphs. The author shows how the wilderness journey in Numbers has a deep relevance for our time and for our personal journeys."--Publisher.